P300 as an auxiliary method in clinical practice: A review of literature (Journal of Health Sciences, 2016)
Cognitive functions can be assessed and followed up over a period of time with cognitive evoked potentials (CEP) P300. In this context, brainstem auditory evoked potentials (BAEP) are most commonly used, but visual evoked potentials (VEP) are utilized as well. The research in this area has demonstrated that these techniques could be used as a supplemental method in diagnostics of numerous diseases such as Alzheimer's disease, mild cognitive impairment, vascular dementia, epilepsy, craniocerebral trauma, Parkinson's disease, multiple sclerosis, and other degenerative diseases. In addition, P300 can also be used as an auxiliary method in the diagnostics of mental disorders conditions such as schizophrenia, panic disorders, narcotic drug addiction, nicotinism, alcoholism, etc. The method assists in monitoring the course of diseases leading to encephalopathy, such as liver and kidney damage and grave anaemia. The advantages of P300 testing are easy application, non-invasiveness, and an unlimited number of potential applications. Moreover, the results obtained with this method are measurable and can be compared.